Epigenetic Regulation of Matrix Metalloproteinase-1 and -3 Expression in Mycobacterium tuberculosis Infection - Moores, Rachel C.; Brilha, Sara; Schutgens, Frans; Elkington, Paul T.; Friedland, Jon S. (Frontiers in Immunology, 2017)
In pulmonary tuberculosis (TB), the inflammatory immune response against Mycobacterium tuberculosis (Mtb) is associated with tissue destruction and cavitation, which drives disease transmission, chronic lung disease and mortality. Matrix metalloproteinase (MMP)-1 is a host enzyme critical for the development of cavitation. MMP expression has been shown to be epigenetically regulated in other inflammatory diseases, but the importance of such mechanisms in Mtb-associated induction of MMP-1 is unknown. We investigated the role of changes in histone acetylation in Mtb-induced MMP expression using inhibitors of histone deacetylases (HDACs) and histone acetyltransferases (HAT), HDAC siRNA, promoter-reporter constructs and chromatin immunoprecipitation assays. Mtb-infection decreased Class I HDAC gene expression by over 50% in primary human monocyte-derived macrophages but not in normal human bronchial epithelial cells (NHBEs). Non-selective inhibition of HDAC activity decreased MMP-1/-3 expression by Mtb-stimulated macrophages and NHBEs, while class I HDAC inhibition increased MMP-1 secretion by Mtb-stimulated NHBEs. MMP-3 expression, but not MMP-1, was downregulated by siRNA silencing of HDAC1. Inhibition of HAT activity also significantly decreased MMP-1/-3 secretion by Mtb-infected macrophages. The MMP-1 promoter region between -2001 and -2942 base pairs from the transcriptional start site was key in control of Mtb-driven MMP-1 gene expression. Histone H3 and H4 acetylation and RNA Pol II binding in the MMP-1 promoter region were increased in stimulated NHBEs. In summary, epigenetic modification of histone acetylation via HDAC and HAT activity has a key regulatory role in Mtb-dependent gene expression and secretion of MMP-1 and -3, enzymes which drive human immunopathology. Manipulation of epigenetic regulatory mechanisms may have potential as a host-directed therapy to improve outcomes in the era of rising TB drug resistance.